2011
DOI: 10.1007/s11629-011-2004-z
|View full text |Cite
|
Sign up to set email alerts
|

Distributed modeling of extraterrestrial solar radiation over the rugged terrains of Pakistan

Abstract: In Pakistan, the solar analogue has been addressed but its surface geographical parameterization has given least attention. Inappropriate density of stations and their spatial coverage particularly in difficult peripheral national territories, little or no solar radiation data, nonsatisfactory sunshine hours data, and low quality of ground observed cloud cover data create a situation in which the spatial modeling of Extraterrestrial Solar Radiation(ESR) and its ground parameterization got sufficient scope. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Figure 6 shows the spatial distribution of Annual T avg in Pakistan during 1970-2009. The spatial trend analysis for Annual T avg showed most significant trends for the regions in the southern part of the country including Balochistan and Sindh provinces and a moderate to increasing trend remained in the Multan and Bahawalpur regions [42]. The Annual T avg showed lower trends for the central part of the country including the upper part of Punjab and plain areas of Khyber Pakhtoonkhwa province (Bahawalpur, Lahore, Faisalabad, Mianwali, Peshawar, Islamabad and Kotli) because of frequent rainfall during the last few decades [49,50].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Figure 6 shows the spatial distribution of Annual T avg in Pakistan during 1970-2009. The spatial trend analysis for Annual T avg showed most significant trends for the regions in the southern part of the country including Balochistan and Sindh provinces and a moderate to increasing trend remained in the Multan and Bahawalpur regions [42]. The Annual T avg showed lower trends for the central part of the country including the upper part of Punjab and plain areas of Khyber Pakhtoonkhwa province (Bahawalpur, Lahore, Faisalabad, Mianwali, Peshawar, Islamabad and Kotli) because of frequent rainfall during the last few decades [49,50].…”
Section: Resultsmentioning
confidence: 93%
“…Heat waves have been reported for being responsible for alteration in temperature trends in the Mediterranean region, according to Galdies [41]. Another logical reason for increasing temperature was highlighted by Ambreen et al [42] as annual Extraterrestrial Solar Radiation (ESR) reduced from south to north in Pakistan; the coastal areas received the maximum amount of ESR that ranged from 11,865-12,326 Mega joule (MJ/m 2 ) while Balochistan Plateau and northern parts of the lower Indus plain received the second highest ERS that ranged from 11,505 to 11,864 (MJ/m 2 ). The results derived in the present study verified the rising trends in respective meteorological stations in the urban areas of Sindh and Balochistan.…”
Section: Resultsmentioning
confidence: 95%
“…Based on the calculation model of SASR on the sloped surface, we can reconsider the corresponding Equations and build the distributed model (or subparagraph integral mathematical model) to calculate PSD and SASR under terrain relief on Mars. Based on the existing theoretical model of solar radiation on Mars [1,2,9,10,26,27,30,32,[37][38][39] and the Astronomical theory on Mars, combining with the theoretical model of solar radiation on Earth [6,8,11,12,14,15,17,63,64,91,[94][95][96][97][98][99][100][101], the SASR model which is suitable for Mars is proposed. It can be given by the following steps:…”
Section: The Law Of Revolution and Rotation Of Marsmentioning
confidence: 99%
“…Few studies have been found on assessment of solar radiation, specifically radiation components over complex terrain in Pakistan, including Ambreen et al (2011), Sultan et al (2014, and Sultan et al (2015). However, no study has been found on the shortwave radiation estimation in the region (Pakistan) particularly complex terrain and the focus study area.…”
Section: Introductionmentioning
confidence: 99%